Cutaneous candidiasis mimicking inverse psoriasis lesion in a type 2 diabetes mellitus patient - Surya, Steven Philip; Dewi, Kardiana Purnama; Regina, Regina (Journal of General - Procedural Dermatology and Venereology Indonesia, 2020)
Background: Type 2 diabetes mellitus (T2DM) condition could affect the skin. The disease is among the greatest risk factors of skin infection such as cutaneous candidiasis and is also associated with autoimmune skin diseases such as psoriasis, which lesion morphologies and predilection areas are quite similar. These similarities are a source of confusion to clinicians. Case illustration: We present a 60-year-old female patient with uncontrolled T2DM and multiple erythematous plaques in the form of shiny lesions at the intertriginous area that developed 1 week prior to her hyperglycemic state. The lesions had recurred at the same site for approximately 10 years and were initially diagnosed as intertriginous candidiasis. Bedside testing revealed a positive Auspitz sign, while the patient’s fungal culture was unremarkable. She was diagnosed with inverse psoriasis (IP) and treated with 0.1% mometasone furoate cream twice a day. The lesions improved but were not completely resolved. Discussion: Inverse psoriasis is a subgroup of psoriasis characterized with thin, non-layered scales, and various predilection areas. The features of the primary lesion may be altered by a patient’s activities, such as use of cleansing soap, which may cause lesions to dry out and ooze, similar to cutaneous candidiasis. Additional examination, such as bedside testing and laboratory work, could help obtain a proper diagnosis. Conclusion: The similar morphologies and predilection areas of IP and cutaneous candidiasis lesions may confuse clinicians. In some limited cases, the correct diagnosis may be obtained by complete history taking, physical examination, and other simple tests.